2014
DOI: 10.1111/asap.12062
|View full text |Cite
|
Sign up to set email alerts
|

Motivated and Displaced Revenge: Remembering 9/11 Suppresses Opposition to Military Intervention in Syria (for Some)

Abstract: We conducted an experimental test of the displaced international punishment hypothesis by testing whether reminding people about 9/11 would increase support for U.S. military intervention in Syria. A community sample of Americans were reminded of 9/11, the terrorist attacks in London in 2005, or were given no reminder before being asked their support for military intervention in Syria. Results indicated that there was a significant suppression effect of desired revenge for the 9/11 attacks on support for milit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Thus, retributivists might not always agree on the exact nature of the ideal punishment for any particular crime. What the existing literature does show is that, on average, individuals who believe in retribution are more likely to support the use of harsh methods to deal with wrongdoers in both the domestic and international realms including capital punishment, torture, and the use of military force (Ellsworth and Ross 1983; Cotton 2000; Carlsmith and Sood 2009; Liberman 2006, 2013, 2014; Gollwitzer et al 2014; Washburn and Skitka 2015).…”
Section: Multitude Of Moralities: Nonliberal Ethics and Attitudes Towmentioning
confidence: 99%
“…Thus, retributivists might not always agree on the exact nature of the ideal punishment for any particular crime. What the existing literature does show is that, on average, individuals who believe in retribution are more likely to support the use of harsh methods to deal with wrongdoers in both the domestic and international realms including capital punishment, torture, and the use of military force (Ellsworth and Ross 1983; Cotton 2000; Carlsmith and Sood 2009; Liberman 2006, 2013, 2014; Gollwitzer et al 2014; Washburn and Skitka 2015).…”
Section: Multitude Of Moralities: Nonliberal Ethics and Attitudes Towmentioning
confidence: 99%
“…Displaced revenge-retaliatory acts that are directed not against the original perpetrator, but rather against a third person who was not directly involved in the original act-is a form of vicarious retribution (Lickel, 2012;Lickel, Miller, Stenstrom, Denson, & Schmader, 2006), and it is conceptually related to (but not identical with) displaced aggression (Marcus-Newhall, Pedersen, Carlson, & Miller, 2000;Miller, Pedersen, Earleywine, & Pollock, 2003). Vicarious retribution occurs whenever those not directly involved in the original offense are involved in the retributive act-such as in the case of James Foley; or in the case of U.S. American citizens endorsing military attacks against targets in the Middle East in response to the 9/11 terrorist attacks (e.g., Gollwitzer et al, 2014;Washburn & Skitka, 2014). Displaced revenge occurs when a victim retaliates against a specific target that merely belongs to the same social category or the same "group" as the original perpetrator.…”
Section: Displaced Revenge and Collective Punishmentmentioning
confidence: 99%
“…In other words, observed effects may be another case of the well-documented pattern whereby reminders of the 9/11 attacks promote outgroup distrust and belligerent foreign policy beliefs (e.g. Landau et al, 2004;Washburn & Skitka, 2015). The fact that responsibility attribution items included mention of the 9/11 attacks casts doubt on the "mere reminder" account as an explanation for observed effects, at least for that outcome, as the 9/11 attacks were at that point salient for all participants.…”
Section: Discussionmentioning
confidence: 99%
“…Such consequences are not limited to the original experience of 9/11 events, but also can follow from reminders of the 9/11 attacks long after they occurred. One relevant study demonstrated that reminders of 9/11 increased preferences of U.S. participants for bellicose foreign policy (specifically, military intervention in Syria) relative to either reminders of the 2005 London bombings or no reminder (Washburn & Skitka, 2015). These are only a few illustrative examples of an impressive body of research that has demonstrated how experience and reminders of the 9/11 attacks have had important implications for outcomes related to intergroup relations.…”
Section: The Present Researchmentioning
confidence: 99%
See 1 more Smart Citation